Community-Based Tourism and Waqf: Measuring Social Impact and Socio-Economic Transformation - Adamu Abubakar Muhammad; Abubakar Sadiq Magaji; Iklima Abubakar Shariff; Bala Babangida (Perwakilan, 2026)
Community-based tourism is increasingly considered as a new engine for sustainable development; However the sustainability of community based tourism relies on the effectiveness of funding, the good governance and the active involvement of local community. This paper examines the role of Waqf (Islamic endowment) in sustainable community-based tourism and aims to quantify the contributions of Waqf in poverty alleviation, education and capacity building, social cohesion among the communities of the destinations, etc. Using various sources from Islamic finance, tourism sustainability and socio-economic development literature, the paper integrates and synthesizes available case studies and empirical data for showing the role of Waqf in establishing community-based tourism sustainable livelihoods while promoting responsible behavior and involvement of all the stakeholders involved. The paper will then address issues on the governance of Waqf in tourism related activities, its transparency, mechanisms of benefit distribution. Ultimately the study can then prove that community-based tourism through Waqf is a major engine for the socio-economic development, local communities’ empowerment while preserving cultural and environment heritage of the destinations, as well as a powerful device for connecting the logic of moral economy to modern business practices. The research recommend here ways to strengthen Waqf contributions in sustainable development and we position Waqf not as a source of money, but as a catalyst for holistic community empowerment.